Energized: Policy innovation to power the transformation of Africa’s agriculture and food system - Malabo Montpellier Panel; Glatzel, Katrin; Tankari, Mahamadou Roufahi; Shah, Meera; Badiane, Ousmane; von Braun, Joachim; Ba, Tidiane Oumar; Tall, Minielle Nabou; Diop, Hawa (International Food Policy Research Institute, 2019)
Energized: Policy innovations to power the transformation of Africa’s agriculture and food system – new report by the Malabo Montpellier Panel highlights the promising energy-related strategies, policies and technologies emerging across Africa's agricultural value chain. The report identifies both successes and challenges in improving the rural poor’s access to energy as part of a broader agriculture sector transformation. Drawing on the government actions of six African countries that were identified as leaders within this space, it also makes recommendations for policy and program interventions that can be replicated across the continent to accelerate this progress.